Anti-Alzheimer’s and Anti-inflammatory Activities of Compounds Isolated from Solanum Mauritianum - Ticona, Luis Apaza; García, Borja Durán; Bastante, Marcos Humanes; Serban, Andreea Madalina; Sánchez, Ángel Rumbero (Planta Medica International Open, 2022)
Solanum mauritianum, commonly known as “Tabaquillo”, was one of the most used plants by tribes from South America as a remedy for headaches. Based on this ethnopharmacological use, a bioguided isolation of compounds with anti-inflammatory and anti-Alzheimer’s activities from S. mauritianum was carried out by measuring the inhibition of NF-κB in C8D1A, Neuro-2a, and EOC 13.31 cells, and by measuring the inhibition of acetylcholinesterase and β-amyloid. This allowed the isolation and characterisation by nuclear magnetic resonance and mass spectrometry of four compounds (1–4). Compounds 1–4 showed NF-κB inhibitory activity with IC50 values of 9.13–9.96, 17.17–17.77, 2.41–2.79, and 1.59–1.93 µM, respectively, while celastrol (the positive control) had an IC50 value of 7.41 µM. Likewise, compounds 1–4 showed anti-Alzheimer’s activity, inhibiting the acetylcholinesterase by 40.33, 20.57, 61.26, and 83.32%, respectively, while galantamine (positive control) showed an inhibition of 90.38%. In addition, concerning the inhibition of β-amyloid aggregation, compounds 1–4 showed an inhibition of 47, 23, 65, and 93%, respectively, while curcumin (positive control) had an inhibition of 71.19%.
Keywords: Solanaceae; Solanum mauritianum; anti-inflammatory; anti-cholinesterase; anti-Alzheimer’s